The Impact of Work from Home Policy for the State Civil Apparatus - Kridawati Sadhana; Ratih Nindita Kirana; Aryo Prakoso Wibowo (Journal of Transformative Governance and Social Justice, 2023)
Since the issuance of the circular letter of the Minister of State Apparatus Empowerment Bureaucratic Reform No. 19 of 2020 concerning the adjustment of the work system of the State Civil Apparatus to prevent the spread of Covid 19 within government agencies, since then Regional Heads have been competing to make calls through policies within their regions to carry out work from home or more popularly called WFH (Work From Home). In this study, a problem was raised as follows, the first is How the Impact of Work From Home for the State Civil Apparatus, and the second is what elements can be classified as the impact of the mayor's policy on work from home for the State Civil Apparatus.  Data collection by asking questions through questionnaires distributed to State Civil Apparatus in the Malang City regional secretariat area. After the data is collected, it will be analyzed using a qualitative approach by classifying it as a result for in-depth analysis and corroborating the cause and effect. The results obtained that the implementation of work from home for the country's civil apparatus also has an impact on employees, organizations, the environment, and society as well as social systems. Employees are given flexible time to work from home and be closer to family, but obstacles to productivity arise when work from home cannot discipline themselves in managing time due to many distractions that occur at home.